(untitled) (Research, Society and Development, 2022)
Depression is the most frequent psychopathology during pregnancy, it is more common in high-risk pregnancies, with about 20% of its occurrence in developing countries. The objective of this paper is to analyze the consequences of gestational depression on women’s health and on the relationship with their child. We carried out a survey with a quantitative approach, and a basic and descriptive nature, with seventy pregnant women of all age groups. Two questionnaires were applied (Self-Report Questionnaire and protocol to assess the bond between mother and child), in person, through an online form, at the institutions UBS Aclimação and at Lar Preservação da Vida, both located in the city of Maringá, state of Pananá. Then, we analyzed the data through descriptive statistics and presented them in tables with frequency distributions and percentage of variables. The research was approved by the ethics committee and follows the rules of Resolution nº 466/2012 CNS. As a result, the interviewees showed a rate of depressive symptoms of 27.14%, with the most prevalent contributing factors being absent parents during the pregnant woman’s childhood (34.29%) and dialogue deprivation (44.29%). This way, we concluded that external and internal factors influence the mental health of the pregnant woman and the development of the bond with the fetus, and the study of these factors is important to create ways to improve the situation, so that it does not harm the pregnant woman or the child.